The Grim Reaper's road map an atlas of mortality in Britain - Shaw, Mary 1968- (Health & society series, 2008)
This impressive full-colour atlas, with over 100 colour-coded and accessible maps, uniquely presents the geography of death in Britain. The first atlas published on this subject for over two decades, this book presents data from more than 14 million deaths over a 24-year period in Britain. The maps detail over 100 separate categories of cause of death, including various cancers, suicides, assault by firearms, multiple sclerosis, pneumonia, hypothermia, falls, and Parkinson's disease, and show how often these occurred in different neighbourhoods. Accompanying each map is a detailed description and brief geographical analysis - the number of people who have died due to each cause, the average age of death and ratio of male to female deaths are listed. Taken as a whole, these provide a comprehensive overview of the geographical pattern of mortality in Britain. This atlas will be essential reading for academics and students of social medicine, sociology of health and illness and epidemiology. It will also be valuable for anyone who wants a better understanding of patterns of mortality within Britain, including medical and healthcare practitioners, policy makers and researchers